Implementación de una antena integrada en tela lycra utilizando tinta Bare Conductive, para la Banda inferior de WI-FI. - Guambaña Tapia, Alex Eduardo (2024)
In the present research work, a Lycra fabric integrated antenna has been implemented using Bare Conductive ink, designed to operate in the lower Wi-Fi band. Through an exploratory study, textile antennas were analyzed, and, by means of the experimental method, a resonant structure at 2.4 GHz was defined. This antenna demonstrates the ability to adapt to various surfaces requiring flexibility, maintaining its functionality and performance in different conditions. The flexible antenna developed in this study has an e-shaped design and uses a coplanar feed. For the substrate, lycra fabric is used on which textile vinyl is applied, which guarantees a homogeneous distribution of the conductive ink. This material has a dielectric constant of εr = 1.50 and a loss tangent of tan δ = 0.0093. In addition, a 50 ohm SMA port is used for the antenna feed. The antenna design and analysis were carried out using CST Studio Suite simulation software. The results obtained show that the final antenna exhibits excellent impedance matching at the 2.4 GHz frequency with a bandwidth of 5.04%. The radiation pattern of the antenna is omnidirectional within the lower WiFi band, highlighting a maximum directivity of 1.748 dBi. The fabrication of the antenna was carried out by screen printing and airbrush scattering methods, using a variety of conductive materials such as copper tape, silver ink, Buddy Paint ink, and Bare Conductive ink for the resonant elements. In addition, experimental measurement of the antenna was performed using a vector network analyzer. This approach allowed evaluating and tuning the antenna performance under practical conditions. Finally, the antenna was integrated into a men's garment, characterized by its flexibility and the use of Lycra fabric in its construction. This step ensures that the antenna adapts comfortably to the users' body structures, maintaining its functionality and optimal performance in wearable technology applications.